Analysis of walkability along Taft Avenue - Capalar, Marie Antonette M.; Garma, Florence Azalea A.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The traffic conditions in Metro Manila are worsening and have become a major concern in the country. Road expansions have become an old-fashioned way to alleviate this problem since more vehicles are bought per year. As a result, walking as a means of transport is becoming more attractive. In this study, the walkability of Taft Avenue, one of the highly congested areas in Metro Manila, will be assessed using the parameters of Global walkability Index (GWI) for Asian countries. The study area is specifically from Pablo Ocampo St. to T.M. Kalaw Avenue where establishments like the World Health Organization (WHO) and National Bureau of Investigation (NBI) is located. The GWI rating is determined through field surveys and pedestrian counts for AM and PM peak hours. The GWI rating is a product of the parameter score, length of the road, and pedestrian count. This rating classified Taft Avenue as moderately walkable, with an overall walkability rating of 61.52%. Some of the undesirable features of the road are the lack of amenities and disability infrastructures, and presence of obstructions along the sidewalks. An additional assessment for the minimum standards set in DPWH DO 65 Series of 2013 and DPWH DO 37 Series of 2009 is also conducted. Availability and condition of sidewalks, pedestrian crossing markings and disability infrastructures are checked and compared for compliance with the set standards. Assessment shows the need for repainting and maintenance of road markings, as well as installation of additional crossings and PWD infrastructures such as handrails. The data gathered in the field surveys are used to formulate other recommendations for the improvement of walking condition in Taft Avenue.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Walking -- Philippines -- Manila; Global Walkability Index (GWI).